2002
DOI: 10.1637/0005-2086(2002)046[1038:pit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pododermatitis in Turkeys

Abstract: Severe pododermatitis is a common lesion in turkeys, unlike in broiler chickens. Both dietary factors (soybean meal, biotin, methionine) and poor litter conditions (wet litter) are documented etiologies of footpad lesions. In the United States and United Kingdom both farm managers and processors monitor lesions. The United Kingdom reports an average footpad relative score higher than that of the United States. In both countries, incidence in toms is higher than in hens. There is no significant difference by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…In the investigations of Hafez et al (2005), male turkeys also had a better foot pad condition in comparison with the turkey hens. The impact of the sex is debated; some authors stated that turkey hens showed a better foot pad health status than the turkey toms due to the higher weight gain of the male birds (Clark et al 2002) and others found no significant relevance in the comparison of the prevalence of FPD between males and females (Martland, 1984). Information about the stocking density was given by the farm managers and averaged 21.5 poults/m 2 during d 3 to 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the investigations of Hafez et al (2005), male turkeys also had a better foot pad condition in comparison with the turkey hens. The impact of the sex is debated; some authors stated that turkey hens showed a better foot pad health status than the turkey toms due to the higher weight gain of the male birds (Clark et al 2002) and others found no significant relevance in the comparison of the prevalence of FPD between males and females (Martland, 1984). Information about the stocking density was given by the farm managers and averaged 21.5 poults/m 2 during d 3 to 5.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors, for example, poor litter condition, especially high litter moisture (Martland, 1984;Clark et al, 2002;Spindler, 2007;Mayne et al, 2007a;Youssef et al, 2010;Abd El-Wahab et al, 2011;Wu and Hocking, 2011) and chemical irritants bound to litter (Martland, 1984), exposition durance (Berk, 2007;Krautwald-Junghanns et al, 2011;Schumacher et al, 2012), stocking density (Clark et al, 2002;Hafez et al, 2005), nutritional deficiencies in biotin (B-complex vitamin) or zinc (Youssef et al, 2012), and genetic factors (Ask, 2010), have been linked to FPD. Within 24 h after birds were initially exposed to wet, not necessary wet and dirty, litter, the first signs of FPD appeared, possibly due to a rapid inflammatory reaction (Mayne et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…During the observations at the slaughterhouse, the investigator scored four different zones on the carcase: (1) the feet, (2) the top dorsal side (articulation of the hock and legs, Figure 1a or a combination of lesion severity and extent (Martland, 1984;Clark et al, 2002;Mayne et al, 2007;Hocking et al, 2008;Youssef et al, 2010). We scored the macroscopic aspect (extent and severity of lesions) on a ten-point scale ranging from 0 (no lesion) to 9 (the most severe lesions) (Table 1), as was proposed in a previous study on broilers (Allain et al, 2009).…”
Section: Scoring Of the Lesions Per Zonementioning
confidence: 99%
“…One of the main methods for assessing animal welfare is based on the measurement of body lesions, as proposed in the Welfare Quality project for broilers and laying hens (Welfare Quality, 2009). In turkey production, some of these body lesions have been studied previously as footpad dermatitis (Martland, 1984;Ekstrand and Algers, 1997;Clark et al, 2002;Mayne, 2005;Hocking et al, 2008;Youssef et al, 2010;Krautwald-Junghanns et al, 2011), other leg and foot abnormities (Swarbrick, 1966;Nestor, 1971;Buffington et al, 1975;Krautwald-Junghanns et al, 2011) and breast lesions (Miner and Smart, 1975;Gonder and Barnes, 1987;Kamyab, 2001;St-Hilaire et al, 2003;Mitterer-Istyagin et al, 2011). As proposed in previous studies, these recordings may be carried out at the farm or at the slaughterhouse (Hocking et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The initial foot pad lesion was considered an entry for an ascending infection which might have subsequently become systemic. Pododermatitis, arthritis and systemic disease were previously reported in domestic (CLARK et al, 2002) and wild turkeys (DAVIDSON et al, 1985) and hawks (MÜLLER et al, 2000). The antibiotic sensitivity test revealed S. aureus growth-inhibition by all (cefalotin, enrofloxacin, erithromycin, florfenicol, gentamycin, neomycin, novobiocin, oxacyllin, penicillin, sulfa + trimethoprim and tetracycline) except penicillin.…”
Section: Este Trabalho Relata Um Surto De Esparavão Em Aves Aquáticasmentioning
confidence: 73%